Insulin signaling: An opportunistic target to minify the risk of Alzheimer's disease. (September 2017) - Pardeshi, Rohit; Bolshette, Nityanand; Gadhave, Kundlik; Ahire, Ashutosh; Ahmed, Sahabuddin; Cassano, Tommaso; Gupta, Veer Bala; Lahkar, Mangala
Graphical abstract: Highlights: Insulin signaling is considered as a major risk factor for AD associated T2DM. Insulin resistance mediates enhanced aggregation and reduced degradation of Aβ. Hyperglycaemia can be considered as possibly associated mechanism between AD and T2DM. Agents targeting insulin signaling shows prominent action on AD associated T2DM. Abstract: Alzheimer's disease (AD) is progressive neurodegenerative disorder characterized by accumulation of senile plaques, neurofibrillary tangles (NFT) and neurodegeneration. The diabetes mellitus (DM) is one of the risk factors for AD pathogenesis by impairment in insulin signaling and glucose metabolism in central as well as peripheral system. Insulin resistance, impaired glucose and lipid metabolism are leading to the Aβ (Aβ) aggregation, Tau phosphorylation, mitochondrial dysfunction, oxidative stress, protein misfolding, memory impairment and also mark over Aβ transport through central to peripheral and vice versa. Several pathways, like enzymatic degradation of Aβ, forkhead box protein O1 (FOXO) signaling, insulin signaling shared common pathological mechanism for both AD and DM. Recent evidence showed that hyperinsulinemia and hyperglycemia affect the onset and progression of AD differently. Some researchers have suggested that hyperglycemia influences vascular tone, while hyperinsulinemia may underlie mitochondrial deficit. The objective of this review is to determine whether existing evidence supports the concept that impairment in insulin signaling and glucose metabolism play an important role in pathogenesis of AD. In the first part of this review, we tried to explain the interconnecting link between AD and DM, whereas the second part includes more information on insulin resistance and its involvement in AD pathogenesis. In the final part of this review, we have focused more toward the AD treatment by targeting insulin signaling like anti-diabetic, antioxidant, nutraceuticals and dietary supplements. To date, more researches should be done in this field in order to explore the pathways in insulin signaling, which might ameliorate the treatment options and reduce the risk of AD due to DM.